2021
DOI: 10.1109/access.2021.3112240
|View full text |Cite
|
Sign up to set email alerts
|

Does Augmented-Reality Head-Up Display Help? A Preliminary Study on Driving Performance Through a VR-Simulated Eye Movement Analysis

Abstract: Augmented reality heads-up display (AR-HUD) is becoming increasingly popular as a way to keep drivers focusing on roads. By overlaying visuals on the windshield, AR-HUDs improve the drivers' view of the environment outside the car, creating a stronger sense of awareness of the surroundings. However, whether AR-HUD and to what extent different AR-HUD layouts could improve drivers' driving performance are still questionable. Unfortunately, AR-HUD is still at a research stage, not yet fully commercialized. Hence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For example, Bark et al [11] demonstrated that car-based HUD systems featuring navigation arrows projected on a see-through display in front of the driver help maintain the driver's focus on the road, resulting in improved performance and safety [118]. Similar findings have been reproduced with a 2D minimap projected into the corner of the driver's view [83].…”
Section: Wearablementioning
confidence: 97%
“…For example, Bark et al [11] demonstrated that car-based HUD systems featuring navigation arrows projected on a see-through display in front of the driver help maintain the driver's focus on the road, resulting in improved performance and safety [118]. Similar findings have been reproduced with a 2D minimap projected into the corner of the driver's view [83].…”
Section: Wearablementioning
confidence: 97%
“…Lastly, based on the BP neural network between the visual arrangement coding of the head-up display and NASA-TLX, its topological structure is determined, as shown in Figure 6. The meaning of a [1] (x) represents the activation function of the hidden layer in the backpropagation (BP) neural network. A [0] represents the input layer, and A [1] -A [3] represent the hidden layers.…”
Section: Topological Structure Of Bp Neural Networkmentioning
confidence: 99%
“…The meaning of a [1] (x) represents the activation function of the hidden layer in the backpropagation (BP) neural network. A [0] represents the input layer, and A [1] -A [3] represent the hidden layers. A [4] represents the output layer.…”
Section: Topological Structure Of Bp Neural Networkmentioning
confidence: 99%
“…AR HUDs can provide a more intuitive and immersive interface [10], and compared to traditional HUDs, AR HUDs can recognize turn positions earlier [10]. In order to avoid distractions caused by information, it depends on the perceptual form of graphic elements and interfaces on the display [2], [12]. Since vision is a highly complex task, designing information for HUDs must take into account many factors such as color, position, size, light source, and background complexity [9].…”
Section: Introductionmentioning
confidence: 99%